Characteristics of Computer Printed Documents Produced by Different Printing Devices - Boraei , Abeer Sayed Abdou; Al-Akid, Yasser Fouad Abd El-Monem; Tamim, Khaled Abd El-Azeem Mahmoud; Mahmoud, Nesrine Abd El-Rahman (Recent Progress in Science and Technology Vol. 6, 2023)
Forgery has significantly increased and expanded to include the use of computers and printers, allowing even non-experts to create fraudulent printed documents. The printers and photocopiers leave their imprints on the produced documents. Studying the characteristics of different computer printed documents help in identification of the type of the producing output devices (photocopier, inkjet, and laser printers). Each class of printing devices imposed specific criteria on the investigated printed documents. These criteria are class features, but they differ depending on the type of device.